New method for continuous monitoring of concrete E-modulus since casting using an output-only modal identification technique - Azenha, Miguel (2010)
A new methodology that allows the continuous measurement of concrete E- mod-ulus since casting is presented in this paper. This methodology is a variant to the classical reso-nant frequency methods, which have the downside of requiring concrete to be de-mouldable and withstand mechanical impact to start testing. The proposed experimental setup comprises a simply supported beam made-up with an acrylic tube, filled with the concrete to be tested, whose mid-span vertical accelerations induced just by ambient vibrations are continuously mon-itored by an accelerometer. The numerical treatment of the monitored accelerations allows iden-tification of the 1st resonant frequency of the composite beam, which is evolving as concrete hardens. The E-modulus of concrete can thus be directly obtained from the monitored frequen-cy. Besides the description of the overall setup, the results obtained in an experiment in which the concrete E-modulus was quantified also through static tests on the beam and via compres-sive tests in cylinders are presented and discussed.